The influence of training status on the drop in muscle strength after acute exercise - Pingel, J.; Moerch, L.; Kjaer, M.; Langberg, H. (European Journal of Applied Physiology, 2009)
Skeletal muscles fatigue after exercise, and reductions in maximal force appear. A difference in training status between the legs was introduced by unilateral immobilization of the calf muscles for 2 weeks in young men, who were randomly assigned to two groups, either a RUN group (n = 8) that was exposed to prolonged exercise (1-h running: individual pace) or a REST group (n = 12) that did no exercise after immobilization. Cross-sectional area (CSA) of the triceps-surae muscles was calculated by magnetic resonance imaging (MRI), and maximal voluntary contraction (MVC) force of the plantar flexors was measured before and after immobilization and after the running protocol. The CSA of triceps-surae muscles decreased significantly with a 7% reduction in both groups. A significant drop in the MVC of the triceps-surae muscle (10%; P < 0.05) was observed in response to immobilization. When subjected to running exercise immediately after immobilization, the muscle strength of the triceps-surae muscles dropped even further, but just in the immobilized leg (41%; P < 0.05). The present study highlights the importance of determining the muscle endurance when evaluating the effect of immobilization on muscle parameters.